Pengaruh Brand Image terhadap Keputusan Pembelian Produk Mie Gacoan pada Kalangan Mahasiswa Kota Bandung - Ranti Febrianti; Ramadhika, Alda (Jurnal Disrupsi Bisnis, 2024)
This research aims to find out how much influence Brand Image has on the Purchase Decision of Gacoan Noodles among Bandung City Students. To collect data for this research, a questionnaire instrument was used along with quantitative methodology. In this research, 100 respondents were selected randomly using Random Sampling Technique. T test, coefficient of determination (R2), and simple linear regression test were used in this research. Research findings show that brand image has an influence. This influence is shown by the regression equation Y= 18.663 + 0.409 X and a coefficient of determination test of 0.357. This means that brand image (X) and purchasing decisions (Y) are 35.7% with the remaining 64.3% caused by other factors. So based on the existing results, it is said that brand image influences purchasing decisions.